Analisis Semiotika Foto Perempuan Dalam Media Cetak Harian Serambi Indonesia (Edisi Januari Sampai Februari 2015) - M. Ikram Maulanda Anhar; Hamdani M Syam (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
Abstrak. Penelitian ini berjudul “Analsisi Semiotika Foto Perempuan dalam Media Cetak Harian Serambi Indonesia (Edisi Januari sampai Februari 2015)”. Objek dalam penelitian ini adalah sepuluh foto perempuan yang diuat oleh Media Cetak Harian Serambi Indonesia edisi Januari sampai Februari 2015. Penelitian ini menggunakan kerangka analisis semiotika Roland Barthes yang mengacu terhadap dua tanda (konotasi dan denotasi) untuk memahami makna yang terkandung didalam foto-foto perempuan yang di muat Harian Serambi Indonesia. Tujuan penelitian ini adalah untuk mengetahui makna denotatif, konotatif, dan mitos yang terkandung dalam foto perempuan yang dimuat Harian Serambi Indonesia. Pendekatan penelitian menggunakan pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa makna denotasi yang memperlihatkan kegiatan-kegiatan yang dilakukan oleh perempuan dalam menjalani aktivitasnya sehari-hari. Sedangkan, makna konotasi yang muncul memperlihatkan kegiatan-kegiatan yang dilakukan oleh perempuan dalam menjalani aktivitasnya sehari-hari. Kata Kunci: Analisis Semiotika Roland Barthes, Foto Jurnalistik, Perempuan, Harian Serambi Indonesia. Abstract. Serambi Indonesia started to rise since February 9, 1989, the people of Aceh favorite media with a circulation of up to 35,000 copies and is very popular in many circles. In carrying out his duties as a transmitter of information that is actual and factual, Daily foyer Indonesia often featured images of women as complementary news. The issue is whether denotative, connotative and myths contained in the photograph women contained Daily Serambi Indonesia? The research approach used descriptive qualitative approach. This study uses a semiotic analysis of Roland Barthes refers to the two signs (connotation and denotation) to understand the meaning contained in photographs of women contained by foyer as a complement to the story (issue of January to February 2015). The sample used in the study period of ten photos. The results showed that the denotation of meaning that appear in the photographs of women that appeared in the Daily Serambi Indonesia (edition of January to February 2015) shows the activities carried out by women in carrying out their daily activities. Meanwhile, connotations that appear in the photographs of women that appeared in the Daily Serambi Indonesia (edition of January to February 2015) the dominant persuasive to the reader to perform activities that are positive, such as: travel, study hard, farming, blood donation, to become activists and even the police. In addition, Daily Serambi Indonesia often use the image of women as complementary to attract the reader's attention. It was discovered in images of women from the data that researchers take, on a news photo to-1 "Visitor Park cave tour of Japan", the image of the association seen by naked eye from the style of dress worn by a female visitor. In photo 4, 6, 7, and 9, Harian Indonesia foyer dominant display the image frame, which should have less unreasonable or out of context, why choose images of women than men. Suggested for daily photo journalist Porch Indonesia, to improve the quality of image capture news in terms of the meaning of denotation, konotosi and myths, as well as careful in selecting and sorting the image of women that will emerge from photojournalism to be displayed. Society as a reader Daily Serambi Indonesia must critical and not be carried away by the media ideology.